Seat Belt Syndrome - Onuoha, Kelechukwu M.; Ekwe, Kingsley K.; Anosike, Ikechukwu; Akinola, Bolarinwa; Ogedegbe, Felix E. (Nigerian Journal of Orthopaedics and Trauma, 2018)
Seat belt syndrome is a term used collectively for all injuries associated with the use of seat belts during motor vehicular accident. It usually presents with seat belt sign with associated intra‑abdominal, thoracic, pelvic and spinal injuries. A 42‑year‑old male presented to our hospital 15 h after a head‑on collision with an oncoming vehicle. He was the driver of a saloon car and was seatbelted at the time of the accident. He sustained multiple injuries which included blunt abdominal injury, multiple rib fractures and right femoral fracture. Examination revealed the seat belt sign on both anterior chest and abdominal walls and progressive abdominal distension with right femoral fracture. Chest, brain and abdominal computed tomography scans confirmed the diagnosis. He subsequently had an exploratory laparotomy and damage control orthopaedics in which an external fixator was applied to the right femur and a locked intramedullary nail thereafter. He recuperated and discharged home 26 days after the accident. Patients who present with a seat belt sign on the anterior chest or abdominal wall following a motor vehicle accident should be managed with a high index of suspicion for seat belt syndrome. Thus, the presence of any of the injuries mentioned should warrant a search for other associated injuries. With increase in the compliance of seat belt use amongst car users in Nigeria, there will be a rise in seat belt syndrome, There is need to create more awareness about seatbelt syndrome and a classification system would help to know its severity.